ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PRESTASI MAHASISWA DI PERGURUAN TINGGI - Rahardian Okta Pratama; Lindawati Kartika; Andita Sayekti (Perspektif Ilmu Pendidikan, 2018)
IPB is consistently becoming the Top 4 Best Universities based on the result of The Ministry of Research and Higher-Education Assessment Score for three years. Meanwhile, IPB still has the lowest assessment score on student affairs among other three universities. One of the significant components is the student achievements. This research aim (1) to identify the characteristics of the excellent students, (2) to analyze the perceptions about factors that significantly affect student achievement and student achievement itself, (3) to analyze the factors that significantly affect student achievement and student achievement itself, (4) to determine the result of Net Promoter Score of alumni to IPB. This research focused on a case of Department of Management Alumni Graduates of 2009 - 2013 FEM IPB that was conducted in Bogor Agricultural University from January to April 2018. This research used both primary and secondary data. The data analysis of this research was conducted by descriptive analysis, SEM-PLS, and Net Promoter Score. This research resulted that the environmental, physiological, psychological and instrumental factors had a t-statistic as orderly followed by 2.053, 2.031, 2.701, 0.033, whereas these factors were concluded to significantly affect the students` achievement. References BAN-PT. (2008). Naskah akademik akreditasi program studi sarjana. Jakarta: Kemenag. Ditmawa. (2017). Panduan mahasiswa berprestasi Institut Pertanian Bogor. Bogor: Direktorat Kemahasiswaan IPB. Ghozali, I. (2014). Structural equation modeling metode alternatif dengan partial least square (PLS). Semarang: Badan Penerbit UNDIP. Kemenristekdikti. (2017). Pedoman pemilihan mahasiswa berprestasi program sarjana. Jakarta: KementerianRiset dan Pendidikan Tinggi Indonesia. Lemeshow, S., Hosmer, DW., Klarr, J., & Lwanga, S.K. (1990). Adequacy of sample size. Chichester: John Wiley & Sons Ltd. Mailhot, B., & Feeney, S.L. (2017). Perceived parental involvement and academic achievment of college students: The mediating role of academic self-concept. North American Journal of Psychology, 19(3), 685-708. Mirnawati, L. B., & Pribowo, F. S. (2017). Penerapan model pembelajaran SAVI untuk meningkatkan kemampuan berbicara mahasiswa PGSD FKIP Universitas Muhammadiyah Surabaya. Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 1(2), 144-152. Parma, G. P. (2014). Softskill development sebagai konsep dalam kegiatan pengembangan program kemahasiswaan (studi pemetaan dan analisis program kemahasiswaan fakultas ekonomi dan bisnis). Seminar Nasional Riset Inovatif, 2, 285-292. Purba, M. (2009). Analisis pengaruh kualitas pelayanan terhadap prestasi akademik mahasiswa perguruan tinggi X. Skripsi. Bogor: Institut Pertanian Bogor. Purwanto, N. (2013). Psikologi pendidikan. Bandung: Remaja Rosdakarya. Putri, K. P. (2014). Analisis faktor eksternal dan internal yang memengaruhi prestasi mahasiswa (studi kasus alumni program sarjana manajemen FEM IPB. Skripsi. Bogor: Institut Pertanian Bogor. Monkey, S. (2017). Mengenal net promoter score. Diakses dari https://www.surveymonkey .com/ mp/mengenal-net-promoter-score pada tanggal 1 November 2017. Tambunan, H. (2011). Desain dan pengembangan model pembelajaran berbasis softskill. Jurnal Pendidikan Teknologi dan Kejuruan. 13(1), 8-14.